2013
DOI: 10.1016/s0140-6736(13)60851-x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic development as an intervention against malaria: a systematic review and meta-analysis

Abstract: Official URL: http://dx.doi.org/10.1016/S0140-6736(13)60851-X More details/abstract: Background: Future progress in tacking malaria mortality will probably be hampered by the development of resistance to drugs and insecticides and by the contraction of aid budgets. Historically, control was often achieved without malaria specific interventions. Our aim was to assess whether socioeconomic development can contribute to malaria control. Methods: We did a systematic review and meta-analysis to assess whether the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
159
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 51 publications
13
159
0
3
Order By: Relevance
“…1 Although there is a continuing debate over how well wealth indices agree with consumption, 13 they are a pragmatic means to assess SEP rapidly and can theoretically represent long-term SEP, similar to consumption expenditure, because assets are relatively resilient to short-term economic shocks. 6 We observed that the wealth index was sensitive to socioeconomic inequalities in HBR and parasite prevalence, and indeed it is possible that this metric was less subject to FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although there is a continuing debate over how well wealth indices agree with consumption, 13 they are a pragmatic means to assess SEP rapidly and can theoretically represent long-term SEP, similar to consumption expenditure, because assets are relatively resilient to short-term economic shocks. 6 We observed that the wealth index was sensitive to socioeconomic inequalities in HBR and parasite prevalence, and indeed it is possible that this metric was less subject to FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…1 Measuring socioeconomic position (SEP), the suite of social and economic factors that determine the position held by individuals and groups within a society, 2,3 is therefore critical both to studying the socioeconomic determinants of malaria and to most observational malaria research, since SEP confounds many relationships. However, as for many other health outcomes, 4,5 the relative strength of metrics for evaluating the association between SEP and malaria has been little considered.…”
Section: Introductionmentioning
confidence: 99%
“…The causal link between malaria and poverty runs in both directions with the high burden of malaria identified as a driving factor in further impoverishment of people in endemic countries; and poverty being a major contributory factor in malaria infection [5][6][7][8]. No wonder the burden of malaria is highest in the poorest countries of the world [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These data are consistent with other findings in Africa, where age has been strongly associated with malaria infection (detected by RDT or PCR), especially for children aged 0-10 years. 21 However, in low-transmission settings of Domain 2, the opposite trend was found for microscopy (0.2% in 0-14 years age group versus 1.0% in ≥ 15 years age group, P < 0.01). These data demonstrate how the malaria epidemiology can vary according to the ecological environment, the distribution of the vectors species, and human behavior, especially in unstable transmission areas.…”
Section: Resultsmentioning
confidence: 85%